Determinants of Accident Occurrence among Commercial Motor Cycle Riders in Kaloleni Sub-County, Kilifi County, Kenya - Mkaha Zuma, Baya; Ayieko Yonge, Shadrack; Baya Msanzu, Joseph; Udu Yussuf, Rahma (Multidisciplinary Journal of Technical University of Mombasa, 2021)
Motorcycle accidents remain one of the main global concerns despite extensive research and interventions. The African region has the highest road fatality rates globally, in spite of being the least motorized region. Kenya has an estimated road fatality rate of 20.9 per 100,000 people, higher than that of the European region. There has been an increased use of motorcycles in Kenya over the last decade, so has the number of deaths from motorcycle injury. This study was aimed to establish the determinants of accident occurrence among commercial motorcycle riders in Kaloleni sub-County, Kilifi County, Kenya. A self- administered structured questionnaire was used to collect data from 279 commercial motorcycle riders. Factors associated with accident occurrence were analysed using both bivariate and multivariate analysis. Results showed that 29.2% of the respondents had been involved in a road traffic accident in the past 12 months by the time of the study. Factors that were independently associated with motorcycle accidents included riding experience of more than 8 years (p = 0.040), alcohol use (p = 0.040), slippery roads (p = 0.020) and pot holes on roads (p =
Keywords: Commercial motor cycles, Accident occurrence, Determinants, Kilifi County, Kenya